Evaluation of miniscrew angulation in the posterior maxilla using cone-beam computed tomographic image - Henrique M. Villela; Mario Vedovello Filho; Heloísa C. Valdrighi; Milton Santamaria-Jr; Carolina Carmo de Menezes; Silvia A. S. Vedovello
ABSTRACT Objective: This study aimed at evaluating whether changes in the insertion angle is a determining factor in the positioning of the miniscrews body in a region with larger interradicular space in the posterior maxilla. Methods: Analysis of 60 posterior maxillary quadrants were made using images obtained by means of cone-beam computed tomographic image (CBCT), with 0.076-mm voxel, which presented a real miniscrew inserted in the mesial region of the maxillary first molars, serving as reference point for the placement of the virtual miniscrews. Measurements of the distances between roots were made in three points on the body of the virtual miniscrews (A, B and C), at four different angulations, 70o, 60o, 50o and 40o (T1 to T4), in relation to the long axis of the second premolar. This evaluation was made in four groups, selected in accordance with the disposition of the roots of the second premolars and first molars: Group 1 (all types of roots), Group 2 (convergent roots), Group 3 (divergent roots) and Group 4 (parallel roots). Results: There were no statistically significant differences in the measurements of points A, B and C, at the different angles (70o, 60o, 50o and 40o) and in the different groups (p > 0.05). Conclusions: Changes in the insertion angle is not a determinant factor in the positioning of miniscrews body in regions with larger interradicular space in posterior maxilla.